2017
DOI: 10.1002/adfm.201606129
|View full text |Cite
|
Sign up to set email alerts
|

Advent of 2D Rhenium Disulfide (ReS2): Fundamentals to Applications

Abstract: Rhenium disulfide (ReS2) is a two dimensional (2D) group VII transition metal dichalcogenide (TMD). It is attributed with structural and vibrational anisotropy, layer independent electrical and optical properties, and metal-free magnetism properties. These properties are unusual compared with more widely used group VI-TMDs e.g. MoS2, MoSe2, WS2 and WSe2. Consequently, it has attracted significant interest in recent years and is now being used for a variety of applications including solid state electronics, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
288
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(298 citation statements)
references
References 173 publications
10
288
0
Order By: Relevance
“…Ultrathin 2D semiconductors comprising transition metal chalcogenides (TMCs), [1][2][3][4][5][6] hybrid perovskites, [7,8] or group III-VIA compounds [9][10][11] have attracted intense attention as key building blocks for electronics and optoelectronics due to their large specific surface area, tunable optical properties, and quantum confinement effect, which is a result of their ultrathin form. [12][13][14] To produce logic circuits with low power consumption and high integration, p-type semiconductors are desired; as a layered p-type semiconductor with a wide bandgap of 2.7 eV, GeSe 2 can compensate for the rarity of p-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrathin 2D semiconductors comprising transition metal chalcogenides (TMCs), [1][2][3][4][5][6] hybrid perovskites, [7,8] or group III-VIA compounds [9][10][11] have attracted intense attention as key building blocks for electronics and optoelectronics due to their large specific surface area, tunable optical properties, and quantum confinement effect, which is a result of their ultrathin form. [12][13][14] To produce logic circuits with low power consumption and high integration, p-type semiconductors are desired; as a layered p-type semiconductor with a wide bandgap of 2.7 eV, GeSe 2 can compensate for the rarity of p-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of ReS 2 has received special attention due to its recently discovered distinctive properties, which may derive from its electronic structure [15]. However, most of the syntheses are directed to the production of single crystalline layers, or few-layer thin crystals for electronic applications [16]. These ordered compounds have been successfully obtained by chemical vapour deposition (CVD) [17,18], by physical vapour desposition (PVD) [19], and by microwave-induced plasma methods [20].…”
Section: Introductionmentioning
confidence: 99%
“…Once the center of inversion is eliminated in a random alloy, all 33 modes become Ramanactive in principle. There have been very few Raman studies of sulfur-doped ReSe 2 32,42 though Liu et al reported the Raman spectrum of the ReSeS ternary alloy. However, with 33 modes spread over a range of 100-500 cm −1 , the analysis of this spectrum is not trivial.…”
Section: Introductionmentioning
confidence: 99%
“…They belong to the transition metal dichalcogenide (TMD) family reported by Wilson and Yoffe 1 but, unlike more wellknown TMDs, their structure is highly anisotropic in the layer plane and this is reflected in all their physical properties. [2][3][4] The class of van der Waals layered semiconductors with in-plane anisotropy is a topic of great current interest and, besides ReS 2 and ReSe 2 , it includes black phosphorus, [5][6][7] GeS, 8 transition metal trichalcogenides 9 and Sb 2 Se 3 . 10 Proposed applications of ReX 2 (X = S, Se) include plasmonic materials, 11 polarization-sensitive photodetectors with high sensitivity, [12][13][14][15] inverters, 16 catalytic devices, 17,18 and few-layer field effect 19,20 or heterojunction 21 transistor structures.…”
Section: Introductionmentioning
confidence: 99%